Ayah Tiri sebagai Wali Nikah Perspektif Empat Mazhab - Fitri, Riskha; Hadi, Mukhammad Nur (Department of Comparative Mazhab Comparative, Fakulty of Shariah and Law, 2024)
Abstract: Marriage is a physical and mental bond between a man and a woman that aims to form a happy and eternal family. In marriage, some pillars and conditions determine the validity of a marriage. One of them is the presence of a guardian. Islamic Law Pluralism refers to the diversity of views, madzhab, in the application of valid Islamic law. In this case, there are differences of opinion in the fiqh madzhab in determining the law. Therefore, in this study, the author examines the validity of the stepfather as a marriage guardian based on the views of the madzhab imams, with a case study focusing on the Office of Religious Affairs (KUA) of Kraton District, Pasuruan Regency. This research uses a qualitative approach with a comparative analysis method. Data collection was conducted through interviews with the KUA and strengthened by literature review from the fiqh books of the four main madhhabs: Hanafi, Maliki, Shafi'i, and Hanbali. The results of the study reveal that there are different views among the madzhab imams regarding the validity of stepfathers as marriage guardians. Stepfather as a marriage guardian, according to the views of Imam Hanafi and Imam Maliki, allows the stepfather to be a marriage guardian because, according to Imam Maliki, the right of ijbar wali is owned by every Muslim. And according to Imam Hanafi, it is permissible to marry without a guardian or ask someone else to marry him. Meanwhile, according to Imam Hanbali and Imam Syafi'i, a stepfather is not valid as a marriage guardian because a stepfather is not a nasab guardian and does not have the right of ijbar.Keywords: Marriage Guardian, Stepfather, Imams of the Madzhab, Islamic Marriage Law. Abstrak: Pernikahan merupakan ikatan lahir batin antara seorang pria dan wanita yang bertujuan untuk membentuk keluarga yang bahagia dan kekal. Dalam pernikahan terdapat rukun dan syarat yang menentukan sahnya suatu pernikahan tersebut. Salah satunya yaitu adanya wali. Pluralisme Hukum Islam mengacu pada keragaman pandangan, madzhab dalam penerapan hukum islam yang sah. Dalam hal ini terdapat perbedaan pendapat madzhab fiqih dalam menetapkan hukum. Oleh karena itu, pada penelitian ini penulis mengkaji keabsahan ayah tiri sebagai wali nikah berdasarkan pandangan para imam mazhab, dengan studi kasus yang berfokus pada Kantor Urusan Agama (KUA) Kecamatan Kraton, Kabupaten Pasuruan. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis-komparatif. Pengumpulan data dilakukan melalui wawancara dengan pihak KUA, serta diperkuat dengan kajian literatur dari kitab-kitab fiqh empat madzhab utama: Hanafi, Maliki, Syafi’i, dan Hanbali. Hasil penelitian mengungkap adanya perbedaan pandangan di antara imam madzhab terkait keabsahan ayah tiri sebagai wali nikah. Ayah tiri menjadi wali nikah menurut pandangan Imam Hanafi dan Imam Maliki memperbolehkan ayah tiri menjadi wali nikah dikarenakan menurut Imam Maliki hak ijbar wali dimiliki oleh setiap muslim. Dan menurut Imam Hanafi memperbolehkan nikah tanpa wali atau meminta orang lain untuk menikahkannya. Sedangkan menurut Imam Hanbali dan Imam Syafi’i, ayah tiri tidak sah menjadi wali nikah dikarenakan ayah tiri bukan termasuk wali nasab dan tidak memiliki hak ijbar.Kata kunci: Wali Nikah, Ayah Tiri, Imam Mazhab, Hukum perkawinan Islam.